1996
DOI: 10.1016/0165-2427(95)05520-7
|View full text |Cite
|
Sign up to set email alerts
|

Serum haptoglobin as an indicator of the acute phase response in bovine respiratory disease

Abstract: The early stages of the host response to infectious agents include a number of physiologic changes, collectively known as the acute phase response. The acute phase response is comprised of reactions localized at the site of infection, as well as the initiation of systemic responses, which include a rapid increase in the serum concentration of some proteins, known as acute phase proteins (APP). Using polyacrylamide gel electrophoresis, we detected two APP of approximately 22 and 37 kDa molecular weight in sera … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
97
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(110 citation statements)
references
References 21 publications
(19 reference statements)
6
97
0
2
Order By: Relevance
“…Ceruloplasmin, haptoglobin, acid glycoprotein, and probably protein with molecular weight of 34,000 Da have been identified as acute phase proteins (APP) (Gruys et al 1994, Godson et al 1996, and are synthesized through the liver in response to inflammatory cytokines, particularly interleukin-6 (Heinrich et al 1990). Haptoglobin has been identified as the main acute phase protein in cattle and is an important marker of bacterial infection (Eckersall & Conner 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Ceruloplasmin, haptoglobin, acid glycoprotein, and probably protein with molecular weight of 34,000 Da have been identified as acute phase proteins (APP) (Gruys et al 1994, Godson et al 1996, and are synthesized through the liver in response to inflammatory cytokines, particularly interleukin-6 (Heinrich et al 1990). Haptoglobin has been identified as the main acute phase protein in cattle and is an important marker of bacterial infection (Eckersall & Conner 1988).…”
Section: Discussionmentioning
confidence: 99%
“…In bovine respiratory syncytial virus caused experimentally by HEEGARD et al (2000), it was indicated that hp levels increased with the severity of the disease, Saa was the acute phase protein responding more rapidly to the infection, having higher sensitivity than hp. GODSON et al (1996) stated that body temperature increase, disease score and weight loss in herpesvirus type-1 / P haemolytica infection showed positive correlation with hp levels, and the highest hp levels were observed on the 8th day with occurrence of death. ULUTAŞ et al (2011) reported that significant increases were seen in hp and Saa levels in cattle persistently infected with Bovine viral diarrhea virus, and these increases were possibly associated with IL-6 and IL-8 levels in positive acute phase proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a considerable interest has grown in the development of reliable markers that reflect the severity of the disease and may help to predict survival and the course of the disease in pigs. According to the earlier data (10,11,14,17,26,29), it seems that APPs may be potentially useful as early markers of infection in pigs. However, the knowledge about the correlation between the response of various APPs and the disease severity in pigs is still insufficient.…”
Section: Discussionmentioning
confidence: 99%
“…evaluation of treatment efficacy, discrimination between bacterial and viral infections, evaluation of disease severity) has been studied both in humans and animals (1,8,10,13,19). A significant correlation between APP level in serum and the severity of the disease has been previously reported for some infections in humans (10,17), bovines (11), and horses (14). The relationship between serum APP concentration and the extent of pathological lesions was also studied in pigs (26,29,30); however, the knowledge about the kinetics of APP response and the correlation between serum APP, lung pathology, and the course of disease in pigs co-infected with H3N2 swine influenza virus (SIV) and Bordetella bronchiseptica (Bbr) is restricted.…”
Section: Introductionmentioning
confidence: 99%